Interpretation challenges related to thick lowand high-resistivity layers in electrical resistivity surveys - Lejzerowicz, Anna; Pacanowski, Grzegorz; Maślakowski, Maciej (Archives of Civil Engineering, 2026)
Electrical Resistivity Tomography (ERT) is a versatile and widely applied geophysical method for subsurface imaging, but its reliability is strongly influenced by geological conditions. This study discusses principal challenges in surveys within thick low- and high-resistivity complexes, which distort inversion results and complicate hydrogeological and geotechnical interpretation. In low-resistivity packages (e.g., clays, marls), resistivity values are underestimated, while signals from deeper layers are attenuated, often causing downward displacement of boundaries. In high-resistivity environments (e.g., dry sands, silts), thin conductive interbeds are either masked or appear with artificially elevated resistivity values. Both situations reduce interpretational resolution and increase the risk of overlooking critical geological features. The paper emphasizes the role of survey resolution, controlled by electrode spacing, array configuration, and measurement density. Since resolution decreases with depth, small or thin structures are more reliably imaged in the shallow subsurface, whereas deeper horizons are prone to distortions. The integration of ERT results with borehole data is indispensable for constraining ambiguities and validating inversion outcomes. In addition, vertical resistivity-gradient analysis is proposed as a complementary tool, capable of revealing subtle lithological transitions that may remain undetected in conventional resistivity sections. Through case studies, it is shown how thick resistivity packages affect subsurface models and presents strategies for improving interpretation, including optimized survey design, gradient analysis, and borehole correlation. Despite inherent limitations, ERT remains effective for hydrogeological and engineering investigations, provided that methodological constraints and interpretational uncertainties are carefully addressed.
Keywords: Electrical Resistivity Tomography (ERT); geophysical methods; geotechnical investigations; high-resistivity layers; low-resistivity layers; signal attenuation